2013
DOI: 10.1080/09585192.2013.824911
|View full text |Cite
|
Sign up to set email alerts
|

Expatriate stress and burnout

Abstract: With rapid globalization, multinational firms are sending a growing number of employees on foreign assignments. A growing body of research attests to the interest in the stress experienced by these expatriates. The current study focused on a subject rarely addressed in expatriate stress research, namely burnout. Its goals were to demonstrate: (1) the relevance of burnout to expatriates; (2) the difference between stress and burnout; (3) the role played by the perceived importance of expatriates' work; (4) the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 45 publications
0
62
1
1
Order By: Relevance
“…However, our findings might be interpreted in light of previous studies showing that work and career issues are central in expatriates’ lives. For example, work/career opportunities are one of the most common reasons why expatriates decide on expatriate experience (Dickmann et al, 2008; Selmer & Lauring, 2011) and expatriates often have high status jobs (Silbiger & Pines, 2014). Furthermore, high perceived work importance was found to aggravate the impact of stress on burn out (Silbiger & Pines, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our findings might be interpreted in light of previous studies showing that work and career issues are central in expatriates’ lives. For example, work/career opportunities are one of the most common reasons why expatriates decide on expatriate experience (Dickmann et al, 2008; Selmer & Lauring, 2011) and expatriates often have high status jobs (Silbiger & Pines, 2014). Furthermore, high perceived work importance was found to aggravate the impact of stress on burn out (Silbiger & Pines, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For example, some empirical evidence points at the deleterious psychological correlates of expatriation, including heightened psychological distress (Anderzén & Arnetz, 1999; Forster, 1997; Foyle, Beer & Watson, 1998; Silbiger & Pines, 2014; Truman et al 2012), decreased mental well-being, a worse subjective work environment (Anderzén & Arnetz, 1999), more alcohol and substance abuse (Anderzén & Arnetz, 1997; Truman et al, 2012), externalizing problems, such as attention deficit, hyperactivity, impulse control (Truman et al, 2012), and increased depression (Magdol, 2002; Truman et al, 2012). Acknowledging adjustment as a process that happens on different dimensions – general life, interaction with locals, and work (Black & Stevens, 1989), and adjustment being specific on each dimension (Haslberger et al, 2013), the current study aimed to contribute to the understanding of the association between the three dimensions of adjustment and psychological distress.…”
Section: Introductionmentioning
confidence: 99%
“…Alleviating stress is one of the most important keys to the success of an international assignment (Silbiger & Pines, 2014). Stress for the inpatriate can emanate from many factors such as concern regarding their skills and capabilities and the likelihood of coping successfully with the demands and challenges resulting from relocation to the headquarters (Harvey, Ralston, & Napier, 2000).…”
Section: Stressmentioning
confidence: 99%
“…Discussion T he study's low turnout may relate to the fact that psychological service utilization in migrant groups is low, even when distress levels appear high compared to host populations (Selkirk, Quayle, & Rothwell, 2014). Also, expat stress can be moderated by the perception of favorable living conditions (e.g., in California; Shaffer & Harrison, 2001) and the perceived importance of the expat's work (Silbiger & Pines, 2014). Fieldwork during the present study found many Bay Area expats not only satisfied but proud of their work in Silicon Valley and surrounding areas.…”
Section: International Journal Of Transpersonal Studies 15mentioning
confidence: 99%